Apakah Karakter Eksekutif Memoderasi Hubungan Antara Thin Capitalization, Transfer Pricing, Financial Distress dan Penghindaran Pajak? - Vina Auliyaur Rohmah; Fitri Romadhon (Jurnal Akademi Akuntansi, 2023)
Purpose: This research is used to examine the effect of thin capitalization, transfer pricing, and financial distress on tax avoidance with executive character as a moderating variable in hotel, restaurant, and tourism service companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Methodology/approach: The population of this research is 38 companies. Based on the purposive sampling method, the sample in this research was 18 companies. The data analysis method used in this research is the panel data regression analysis method and the data is processed using Eviews software Findings: The results showed that thin capitalization and financial distress had an effect on tax avoidance, while transfer pricing had no effect. The executive character is able to moderate the effect of thin capitalization and transfer pricing on tax avoidance but is unable to moderate the effect of financial distress on tax avoidance. Practical and Theoretical contribution/Originality: This research has important implications for several parties, one of which is for regulators, namely the results of this study indicate that tax regulations need to be tightened so that opportunities or loopholes for tax avoidance can be minimized. Research Limitation: This research is limited to service companies, especially in the hotel, restaurant, and tourism sectors. Besides that, the executive characteristic variable in this study was only measured in relation to the executives' risk preferences in decision making.